Spoken metadiscourse in Malaysian ESL job interviews - Syamimi Turiman,; Normah Abdullah,; Noorzan Mohd Noor, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Various job interview skills training have been carried out to prepare students for employment. However, the outcome of job interviews is questionable, as one of the reasons for unemployment among Malaysian graduates is their inability to communicate competently in job interviews. The Malaysia Education Blueprint 2015-2025 (Higher Education) stated that unemployed graduates were also lacking in a strong command of English. Since job interviews are placed heavily on verbal exchanges between the interviewer and job candidate, the role that language plays in interaction is worth exploring. This paper investigates spoken metadiscourse in 16 actual first-stage technical and non-technical Malaysian ESL job interviews. Corpus linguistics was employed for data analysis. An adapted framework of spoken metadiscourse is employed to analyse the types and frequencies of textual and interpersonal metadiscourse in the corpus. The findings revealed that both textual and interpersonal metadiscourse were used, but there are variations in the distribution and composition of metadiscourse in the two categories across disciplines. Excessive use of metadiscourse was found to impede communication flow instead of assisting speakers to be persuasive in their speech. This implies the need for targeted instruction on metadiscourse, specifically among language learners in higher learning institutions to facilitate appropriate usage of metadiscourse in speech.